'Ending the Silence': Addressing the Legacy of Displacement in Northern Ireland's 'Troubles'. (11th April 2021) - Gilmartin, Niall
: Though transitional justice measures are increasingly used to address displacement, particularly restitution programmes and truth-telling initiatives, the issue of addressing the long-term impact of displacement on individuals, communities and wider society represents significant challenges for peacebuilding processes. Based on in-depth interviews with those who suffered displacement in Northern Ireland's 'Troubles', this article seeks to explore the marginalized and often silenced narratives of those displaced, shedding light on the multi-layered short- and long-term harms and consequences of displacement for individuals, families and community relations. The article's argument is twofold: first, that experiences of displacement should be considered as a form of conflict-related harm and trauma and those displaced recognized as victims. And second, that 'storytelling' and other bottom-up acknowledgement projects are seen by victims and survivors as an effective vehicle to 'break' the silence, end the denial and advance their pursuit of recognition and acknowledgement.